Facet‐Dependent Electrical Conductivity Properties of Silver Oxide Crystals. Issue 3 (10th January 2017) - Tan, Chih‐Shan; Chen, Ying‐Jui; Hsia, Chi‐Fu; Huang, Michael H.
Abstract: Ag2 O cubes, truncated octahedra, rhombic dodecahedra, and rhombicuboctahedra were synthesized in aqueous solution. Two tungsten probes were brought into contact with a single particle for electrical conductivity measurements. Strongly facet‐dependent electrical conductivity behaviors have been observed. The {111} faces are most conductive. The {100} faces are moderately conductive. The {110} faces are nearly non‐conductive. When electrodes contacted two different facets of a rhombicuboctahedron, asymmetrical I–V curves were obtained. The {111} and {110} combination gives the best I–V curve expected for a p‐n junction with current flowing in one direction through the crystal but not in the opposite direction. Density of states (DOS) plots for varying number of different lattice planes of Ag2 O match with the experimental results, suggesting that the {111} faces are most electrically conductive. The thicknesses of the thin surface layer responsible for the facet‐dependent properties of Ag2 O crystals have been determined. Abstract : Strongly facet‐dependent electrical conductivity behaviors have been observed in Ag2 O crystals. When electrodes contacted any two different facets of a rhombicuboctahedron, asymmetrical I–V curves were obtained. Density of states plots for varying number of different lattice planes of Ag2 O match with the experimental results, suggesting that the {111} faces are most electrically conductive.